Prediction of risk factors for intraoperative hypotension during general anesthesia undergoing carotid endarterectomy - Jia, Yitong; Feng, Guang; Wang, Zheng; Feng, Yao; Jiao, Liqun; Wang, Tian-Long (Frontiers in Neurology, 2022)
Objective Carotid endarterectomy (CEA) has been considered as “gold standard” treatment for patients with significant carotid stenosis Intra-operative hypotension was a risk factor for post-operative complications in patients undergoing CEA. This study aimed to investigate the predictors for intra-operative hypotension during CEA. Methods This retrospective study included consecutive patients underwent CEA from June 1, 2020 to May 31, 2021 in the neurosurgery department of Xuanwu Hospital, Capital Medical University. The intraoperative hypotension was defined as blood pressure (BP) of 20% below standard value for longer than 5 min. Univariable and multivariable analyses were performed to identify the prediction of risk factors for intraoperative hypotension. Results Overall, 367 patients were included, and 143 (39.0%) patients had hypotension during CEA procedure. Univariate analysis indicated Grade 3 hypertension (P = 0.002), peripheral artery disease (P = 0.006) and shunting (P = 0.049) were associated with occurrence of intraoperative hypotension during CEA procedure. On multivariable analysis, Grade 3 hypertension (P = 0.005), peripheral artery disease (P = 0.009), and shunting (P = 0.034) were all found to be independent predicting factors of hypotension during the CEA process. Conclusion Intraoperative hypotension is a dynamic phenomenon may be affected by patients with grade 3 hypertension, peripheral artery disease and intra-operative shunting. It is necessary to pay special attention to these patients, both intraoperatively and postoperatively, to improve the final clinical outcome.